2022
DOI: 10.3897/zookeys.1104.81403
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic study on the genus Stenochironomus Kieffer from the Baishanzu Nature Reserve, China (Diptera, Chironomidae)

Abstract: During the summer of July to September 2020, a biodiversity survey on Chironomidae of Baishanzu Nature Reserve, China was made. In total, five Stenochironomus taxa/species were discovered, of which two belong to undescribed species and one (S. okialbus Sasa, 1990) is reported for the first time from China. The male adults of two new species are described and illustrated. Stenochironomus annulus Song & Qi sp. nov. is distinguished in having a wing with two dark spots restricted to the fork area of FCu and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In insects, color pattern often refers to pigmentation differences—for example, the pigmentation intensity in the body, legs, and wings; uneven membrane thickness; venation; and hair placement—which are often used to distinguish sexes, populations, and species. As in Chironomidae species, color pattern is the main criterion for the identification of some species of Ablabesmyia Johannsen, 1905 [ 44 ]; Cricotopus van der Wulp, 1874 [ 45 , 46 ]; Djalmabatista Fittkau, 1968 [ 47 ]; Metapelopia Silva, Oliverira & Trivinho-Strixino, 2014 [ 48 ]; and Stenochironomus Kieffer, 1919 [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In insects, color pattern often refers to pigmentation differences—for example, the pigmentation intensity in the body, legs, and wings; uneven membrane thickness; venation; and hair placement—which are often used to distinguish sexes, populations, and species. As in Chironomidae species, color pattern is the main criterion for the identification of some species of Ablabesmyia Johannsen, 1905 [ 44 ]; Cricotopus van der Wulp, 1874 [ 45 , 46 ]; Djalmabatista Fittkau, 1968 [ 47 ]; Metapelopia Silva, Oliverira & Trivinho-Strixino, 2014 [ 48 ]; and Stenochironomus Kieffer, 1919 [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have successfully demonstrated the Chironomidae species' delimitation using tree-based and distancebased molecular methods; however, the threshold of distance-based methods for the species between the chironomid genera varies. For instance, Lin et al (2015) set the threshold for Tanytarsus species at 4-5%, Giłka, et al (2018) set the threshold for Tanytarsus mendax group at 1-6%, Song et al (2017) set the threshold for Polypedilum species at 5-8%, and Song et al (2022) set the threshold for Stenochironomus species at 4-6%. Although in the absence of a more comprehensive DNA library for Zavrelia species, it is still too early to set a threshold for the species of this genus, the gap of 8% obtained in this study, based on the distance-based methods (i.e., ABGD and ASAP), is large enough (i.e., larger than previous studies) to support delimitation of Z. parapentatoma from that of Z. pentatoma.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Chironomidae have evolved a diverse range of pigmentation patterns on different body parts, including the abdomen, thorax, wings, and legs [ 11 , 12 , 13 ]. The genus Stictochironomus is widely distributed, occurring in all biogeographical regions except Antarctica, and is characterized by a combination of distinctive wing and leg markings, lack of frontal setae, conical scutal tubercle, fused tibial combs, usually with only one spur, and a distally flattened gonostylus with mobile inferior volsella bent laterally [ 13 ].…”
Section: Introductionmentioning
confidence: 99%